Renewable energy project success: Internal versus external stakeholders' satisfaction and influences of power‐interest matrix. (5th May 2022) - Maqbool, Rashid; Rashid, Yahya; Ashfaq, Saleha
Abstract: Stakeholders satisfaction, as well as an effective involvement, is of utmost importance for any mega project, when it comes to the public concerning projects this role becomes more essential. In the case of developing countries where the political, economic and administrative settings are challenging, managing all the key stakeholders satisfaction for prosperous projects becomes extremely intricated, no matter even it is about sustainable and renewable energy projects. Studies have been conducted on project governance and shareholder relationships, nevertheless, the role of power‐interest matrix in maximizing stakeholder satisfaction on renewable energy projects has not been fully explored in the literature. This research was attempted to investigate the direct and indirect influencing mechanisms of the stakeholders satisfaction in conjunction with five critical success factors (CSFs) (namely communication factors, team factors, technical factors, organizational factors and environmental factors) in the renewable energy projects. Alongside a direct link of the CSFs in renewable energy projects, an indirect influence of both the internal and external stakeholders satisfaction has been also checked in this research. A quantitative approach was used to collect the questionnaire survey based data from the professionals working in the renewable energy industry of Pakistan. A snowball sampling technique was used to collect a total of 565 valid responses from the professionals working on medium and large scale renewable energy projects. The structural equation modelling (SEM) technique was used to perform the data analysis and provide inferences between the direct impacts of CSFs and indirect influences of internal and external stakeholders satisfaction in the renewable energy projects. The first stage of the SEM analysis depicts the direct impacts of the CSFs on renewable energy projects. However, in the second stage, though the mediating role of internal stakeholders satisfaction was observed in between all the CSFs and project success, external stakeholders satisfaction was found to be significantly mediating only between the communication factors and environmental factors, and renewable energy project success. Though the findings provide useful guidelines for the professionals, policymakers and administrators that in order to have prosperous renewable energy projects the influence of both the internal and external stakeholders satisfaction is important alongside CSFs, however, the role of internal stakeholders satisfaction is more critical to consider for such sustainable projects.